The role of atlantic ocean-atmosphere coupling in affecting North Atlantic oscillation variability - Czaja,A; Robertson,AW; Huck,T (2003)
We review the role of ocean-atmosphere interactions over the Atlantic sector in North Atlantic Oscillation (NAO) variability. The emphasis is on physical mechanisms, which are illustrated in simple models and analyzed in observations and numerical models. Some directions of research are proposed to better assess the relevance of Atlantic air-sea interactions to observed and simulated NAO variability.